Rational Voters and Emotional Voters: Analysis of Socio-Psychological Factors in Voting Behavior in the 2024 Presidential Election - Hunawa, Robby; Polinggapo, Jefri (Public Policy Journal, 2025)
The 2024 Presidential Election in Indonesia reflects the increasinglycomplex dynamics of democracy, marked by the increasing role of social media,identity-based campaigns, and candidate personalization. This study aims toanalyze the socio-psychological factors that influence voting behavior, identifythe characteristics of rational and emotional voters, and examine the implicationsof the dominance of emotional behavior on the quality of electoral democracy.The approach used is a mixed-method, through a quantitative survey of youngvoters as well as in-depth interviews and analysis of digital campaign content. Theresults of the study show that factors such as identity affiliation, emotionalcloseness to candidates, and the intensity of social media exposure play asignificant role in shaping voting behavior. Rational voters tend to consider thetrack record and work programs of candidates, while emotional voters are moreinfluenced by symbolism, emotional narratives, and personal perceptions. Thesefindings indicate that the dominance of emotional behavior in elections has thepotential to weaken the quality of electoral democracy because politicaldecisions are often not based on informative rational considerations. This studyrecommends the importance of increasing political literacy, especially amongyoung voters, as well as the development of more ethical and educationalpolitical communication strategies to strengthen the foundations of a healthydemocracy that is oriented towards quality leadership.